2016
DOI: 10.1038/srep21794
|View full text |Cite
|
Sign up to set email alerts
|

A new type of vanadium carbide V5C3 and its hardening by tuning Fermi energy

Abstract: Transition metal compounds usually have various stoichiometries and crystal structures due to the coexistence of metallic, covalent, and ionic bonds in them. This flexibility provides a lot of candidates for materials design. Taking the V-C binary system as an example, here we report the first-principles prediction of a new type of vanadium carbide, V5C3, which has an unprecedented stoichiometry in the V-C system, and is energetically and mechanically stable. The material is abnormally much harder than neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…, and VC have been synthesized and investigated for many years. 180 Boiling points of V 2 O 5 and VC are 2030 and 3900 1C, respectively. The reduction potentials of V 3+ to V 2+ and V 2+ to V are À0.26 and À1.18 V, respectively.…”
Section: (K) Vanadium (V)-mofmsmentioning
confidence: 99%
“…, and VC have been synthesized and investigated for many years. 180 Boiling points of V 2 O 5 and VC are 2030 and 3900 1C, respectively. The reduction potentials of V 3+ to V 2+ and V 2+ to V are À0.26 and À1.18 V, respectively.…”
Section: (K) Vanadium (V)-mofmsmentioning
confidence: 99%
“…A deep valley close to the Fermi level can be seen in the WC DOS curve. In general, such valley is called pseudogap (Xing et al, 2016). The electronic states below the valley are bonding states, and those above the valley are antibonding states.…”
Section: Bonding and The Density Of States (Dos) Of Wcmentioning
confidence: 99%
“…It is suggested that the high hardness of refractory and transition metal carbides may be determined more by the nature of the bonding than by the microstructure features (Jhi et al, 1999). A number of studies have predicted that the hardness of refractory and transition metal carbides could be increased by tuning the valence electron concentration and the Fermi energy (Jhi et al, 1999, Xing et al, 2016. However, there is little evidence to demonstrate the success of enhancing tungsten carbide hardness by alloying and adjusting the Fermi energy, although lots of work has investigated the band structure and electronic properties of tungsten-carbidebased compounds (Suetin et al, 2009;Sahraoui et al, 2004;Suetin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, many attempts have been done to purify high quality vanadium carbide by presenting different binary model system such as VC, V 2 C, V 4 C 3 , V 6 C 5 , and V 8 C 7 . For more details, see [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%